2019
DOI: 10.21873/anticanres.13899
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Intraoperative Pulmonary Wedge Resection of Tumor Site Before Lobectomy for Early Lung Adenocarcinoma

Abstract: Background/Aim: Circulating tumor cells (CTCs) are tumor cells shed from tumor sites and circulate in the peripheral blood. CTCs can be a surrogate biomarker of recurrence and prognosis. Because surgical manipulation could promote CTCs, it is important to reduce CTCs during surgery. This study aimed to evaluate the effectiveness of intraoperative wedge resection of the tumor site before lobectomy. Patients and Methods: A total of 297 resected stage I lung adenocarcinoma patients were retrospectively reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Huang et al reported that preoperative biopsy was an independent factor influencing overall recurrence and that it worsened the disease-free survival of patients with stage I adenocarcinoma, as determined by multivariate analysis adjusted by PSM [19]. As mentioned, Yasukawa et al reported that intraoperative partial pulmonary resection before lobectomy decreased the recurrence rate and improved RFS of earlystage lung adenocarcinoma patients [16].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Huang et al reported that preoperative biopsy was an independent factor influencing overall recurrence and that it worsened the disease-free survival of patients with stage I adenocarcinoma, as determined by multivariate analysis adjusted by PSM [19]. As mentioned, Yasukawa et al reported that intraoperative partial pulmonary resection before lobectomy decreased the recurrence rate and improved RFS of earlystage lung adenocarcinoma patients [16].…”
Section: Discussionmentioning
confidence: 96%
“…Wei et al showed that the vein-first ligating technique was better than the artery-first technique for lobectomy, in terms of prognosis and reduction of CTCs, for patients with NSCLC [15]. Yasukawa et al found that partial resection before lobectomy decreases the recurrence rate and improves RFS of patients with early-stage lung adenocarcinoma [16]. Partial resection was used to create a tumor-free environment before In comparing the preoperative and intraoperative biopsies, Taniguchi et al reported that a preoperative biopsy did not worsen prognosis relative to a lung resection biopsy in patients with cTanyN0M0 NSCLC, as revealed by multivariate analysis [17].…”
Section: Discussionmentioning
confidence: 99%
“…The CTCs positive in hepatocellular carcinoma (HCC) patients after liver resection has a significantly higher risk of recurrence compared to those who were CTCs negative, and the concept of CTCs being potential seeds of metastatic dissemination [17]. There are studies demonstrated that the surgical resection may increase the dissemination of tumor cells into the circulation [13,14]. So, it is critical to know CTCs counts into the blood stream that dissemination from the primary tumor through surgical intervention to predict recurrence and metastasis, or judgement if chemotherapy is necessary after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lung resection has been reported to be safe with minimal complications, and mortality has rarely been reported 35,36 . Most patients underwent wedge resection, while lobectomy was performed only in a few cases 36,37 …”
Section: Lung Oligometastasismentioning
confidence: 99%
“…Furuse et al 40 reported that patients with oligometastasis with a solitary or a few lesions, especially in the lung, can benefit from surgery. The median OS after initial therapy and lung resection was reported to range from 52 to 121 months and from 27 to 47 months, respectively 36,37,39,41,42 . Thomas et al 41 reported that the median OS after initial treatment was significantly longer for patients with lung recurrence than those with liver recurrence among patients with surgery (92.3 vs. 32.5 months).…”
Section: Lung Oligometastasismentioning
confidence: 99%